Acute Hemodynamic Effects and Tolerability of Phosphodiesterase-1 Inhibition With ITI-214 in Human Systolic Heart Failure. (31st August 2021) - Gilotra, Nisha A.; DeVore, Adam D.; Povsic, Thomas J.; Hays, Allison G.; Hahn, Virginia S.; Agunbiade, Tolu A.; DeLong, Allison; Satlin, Andrew; Chen, Richard; Davis, Robert; Kass, David A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: PDE1 (phosphodiesterase type 1) hydrolyzes cyclic adenosine and guanosine monophosphate. ITI-214 is a highly selective PDE1 inhibitor that induces arterial vasodilation and positive inotropy in larger mammals. Here, we assessed pharmacokinetics, hemodynamics, and tolerability of single-dose ITI-214 in humans with stable heart failure with reduced ejection fraction. Methods: Patients with heart failure with reduced ejection fraction were randomized 3:1 to 10, 30, or 90 mg ITI-214 single oral dose or placebo (n=9/group). Vital signs and electrocardiography were monitored predose to 5 hours postdose and transthoracic echoDoppler cardiography predose and 2-hours postdose. Results: Patient age averaged 54 years; 42% female, and 60% Black. Mean systolic blood pressure decreased 3 to 8 mm Hg ( P <0.001) and heart rate increased 5 to 9 bpm ( P ≤0.001 for 10, 30 mg doses, RM-ANCOVA). After 4 hours, neither blood pressure or heart rate significantly differed among cohorts (supine or standing). ITI-214 increased mean left ventricular power index, a relatively load-insensitive inotropic index, by 0.143 Watts/mL 2 ·10 4 ( P =0.03, a +41% rise; 5–71 CI) and cardiac output by 0.83 L/min ( P =0.002, +31%, 13–49 CI) both at the 30 mg dose. Systemic vascular resistance declined with 30 mg (–564 dynes·s/cm– 5, P <0.001) and 90 mg (–370, P =0.016). Diastolic changes were minimal, and no parameters were significantly altered with placebo. ITI-214 was well-tolerated. Five patients had mild-moderate hypotension or orthostatic hypotension recorded adverse events. There were no significant changes in arrhythmia outcome and no serious adverse events. Conclusions: Single-dose ITI-214 is well-tolerated and confers inodilator effects in humans with heart failure with reduced ejection fraction. Further investigations of its therapeutic utility are warranted. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03387215.